PENGARUH AUGMENTED REALITY BERBASIS WEB DENGAN MODEL PROBLEM BASED LEARNING TERHADAP SIKAP KONSERVASI PESERTA DIDIK - Dwi Ratnasari; Mahrawi Mahrawi; Indria Wahyuni; Vina Risdatika (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims to determine the effect of using Web-based Augmented Reality media with a Problem Based Learning model on the conservation attitude of students in class X MIPA on Biodiversity Materials. The method used in this research is a quasi-experimental method. The research population was students of class X SMAN 4 Serang City and the samples used were four classes, namely class X MIA 1 and 3 as the experimental class and X MIA 2 and 4 as the control class. The sampling was done by using random sampling. The instrument used is a question of conservation attitudes. The data analysis technique used the independent sample t test. Results Based on the research, it was found that the results of hypothesis testing based on the independent sample test output table in the equal variance section were assumed to be known for the Sig. (2-tailed) value of 0.00 and less than 0.05. It can be said that H0 is rejected and H1 is accepted, this shows that there is a significant effect between the use of web-based augmented reality media and problem-based learning models on the conservation attitude of students at SMAN 4 Serang City.